Pemberian ASI Eksklusif Berhubungan dengan Kejadian Stunting pada Balita di Pulau Mandangin Kabupaten Sampang - Sri Sumarni; Nelyta Oktavianisya; Emdat Suprayitno (Jurnal Riset Hesti Medan, 2020)
Stunting is a chronic condition that shows stunted growth and development due to prolonged nutritional deficiencies. Lack of nutritious food intake in babies born normally can cause stunting. Breast milk is a source of nutrition suitable for digestive conditions in infants. Breastfeeding given <6 months contributes to an increased risk of stunting. This study aims to determine the relationship of exclusive breastfeeding with the incidence of stunting on Mandangin Island. The study design was cross-sectional. The sample of this study involved 90 mothers who have children aged 2-5 years. The sampling technique is a simple random sampling technique. Data collection obtained directly from the main source (primary data) is done by interview using a questionnaire. The test used is Chi-Square. The results showed that mothers who did not give exclusive breastfeeding were 47.8% and stunting children were 55.6%. Statistical test results with chi-square p-value = 0,000 (p <0.05) with an OR value of 3.750 which means that children who are not exclusively breastfed have a risk of 3.7 times higher than children who are exclusively breastfed . There is an exclusive ASI relationship with the stunting incident on Mandangin Island.